COMMUNICATIVE LANGUAGE TEACHING: PRINCIPLES AND EVOLUTION: COMMUNICATIVE LANGUAGE TEACHING: PRINCIPLES AND EVOLUTION - A.Rzamuratova, A.Rzamuratova; Saparov, Salamat (Журнал иностранных языков и лингвистики, 2025)
Communicative Language Teaching (CLT) is a prevalent methodology in foreign language instruction that emphasizes the enhancement of learners’ proficiency in utilizing language for authentic communication. Originating in the 1970s in Western Europe, Communicative Language Teaching signifies a transition from conventional, structure-oriented approaches, such as grammar-translation and audio-lingual methods, to a more functional and learner-centered framework. It underscores communication as both the method and objective of language acquisition, seeking to endow learners with communicative competence—the capacity to utilize language suitably across various social circumstances. [6] This article delineates CLT, investigates its fundamental principles, and analyzes the notion of communicative competence, referencing underlying ideas and practical ramifications for English as a Foreign Language (EFL) education.